Serological markers of extracellular matrix remodeling predict transplant‐free survival in primary sclerosing cholangitis. Issue 2 (30th May 2018) - Nielsen, M. J.; Thorburn, D.; Leeming, D. J.; Hov, J. R.; Nygård, S.; Moum, B.; Saffioti, F.; Gilja, O. H.; Boberg, K. M.; Mazza, G.; Røsjø, H.; Pinzani, M.; et al.
Summary: Background: Primary sclerosing cholangitis is a progressive liver disease with a remarkably variable course. Biomarkers of disease activity or prognostic models predicting outcome at an individual level are currently not established. Aim: To evaluate the prognostic utility of four biomarkers of basement membrane and interstitial extracellular matrix remodeling in patients with primary sclerosing cholangitis. Methods: Serum samples were available from 138 large‐duct primary sclerosing cholangitis patients (of which 102 [74%] with IBD) recruited 2008‐2012 and 52 ulcerative colitis patients (controls). The median follow‐up time was 2.2 (range 0‐4.3) years. Specific biomarkers of type III and V collagen formation (PRO‐C3 and PRO‐C5, respectively) and type III and IV collagen degradation (C3M and C4M, respectively) were assessed. The Enhanced Liver Fibrosis test, including procollagen type III N‐terminal peptide, tissue inhibitor of metalloproteinase‐1 and hyaluronic acid was assessed for comparison. Results: All markers were elevated in primary sclerosing cholangitis compared to ulcerative colitis patients ( P < 0.001). PRO‐C3 showed the largest difference between the two groups with a threefold increase in primary sclerosing cholangitis compared to ulcerative colitis patients. Patients with high baseline serum levels of all markers, except C3M, had shorter survival compared to patients with low baseline serum levels ( P < 0.001). Combining PRO‐C3 and PRO‐C5 the odds ratio for predicting transplant‐free survival was 47 compared to the Enhanced Liver Fibrosis test's odds ratio of 11. Conclusions: Extracellular matrix remodeling is elevated in primary sclerosing cholangitis patients compared to ulcerative colitis patients. Furthermore, the interstitial matrix marker PRO‐C3 was identified as a potent prognostic marker and an independent predictor of transplant‐free survival in primary sclerosing cholangitis.